Trends of national and sub-national burden attributed to kidney dysfunction risk factor in Iran: 1990-2019 - Nejadghaderi, Seyed Aria; Saeedi Moghaddam, Sahar; Keykhaei, Mohammad; Shobeiri, Parnian; Rezaei, Negar; Rezaei, Nazila; , GBD 2019 Iran Kidney Dysfunction Collaborators; Naghavi, Mohsen; Larijani, Bagher; Farzadfar, Farshad; Nejadghader, Seyed Aria; Moghaddam, Sahar Saeedi; et al. (Frontiers in Endocrinology, 2023)
Background: Kidney dysfunction is a risk factor for cardiovascular disease, and chronic kidney disease. Herein, we aimed to describe the attributable burden of kidney dysfunction at the national and sub-national levels in Iran. Methods: The Global Burden of Disease (GBD) 2019 data on deaths, disability adjusted life years (DALYs), years of life lost, and years lived with disability of kidney dysfunction risk factor by age and sex at the national and provincial levels over 1990-2019 were extracted. Also, risk exposure was reported by summary exposure value (SEV) with a range from 0 to 100. The estimated values were based on a comparative risk assessment framework. Results: In 2019, the age-standardized death rate and age-standardized DALYs rate attributable to kidney dysfunction were 58.2 (95% uncertainty interval 48.8-68.1) and 1127.2 (981.1-1282.7) per 100,000 population in Iran, respectively. Also, Sistan and Baluchistan (1729.3 [1478.3-2006.4]) and Tehran (681.9 [571.4-809.8]) had the greatest and lowest age-standardized DALYs rate, respectively. Nationally, SEVs increased from 22.8 to 26.2. The age-standardized burden attributable to kidney dysfunction had a positive association with age advancing. The attributable age-standardized deaths and DALYs rates in all socio-demographic index regions decreased over 1990-2019. Also, the highest and lowest attributable age-standardized DALYs rate of kidney dysfunction came from ischemic heart disease and peripheral artery disease in 2019, respectively. Conclusion: Although the attributed age-standardized DALYs and death has decreased over 1990-2019, the risk exposure has increased and it is still a crucial risk factor in Iran. Therefore, policymakers should consider preparing a preventive program that takes into account different levels of prevention from kidney dysfunction.